Fresno County Courthouse Park: Courthouse, Statues and Sculptures - Watkins, Howard::::::::: (1989)
"Boy and the Boot" Sculpture Fountain located near Van Ness and Fresno Streets Now located at Fresno County Plaza Lower Level (M and Tulare Streets